USING INNOVATIVE TEACHING TECHNOLOGIES AS TOOLS FOR THE FORMATION OF PROFESSIONAL COMPETENCIES IN THE TEACHING OF CLINICAL CYCLE DISCIPLINES IN VETERINARY - F I Vasilevich; N V Pimenov; O E Davydova (Universitas Brawijaya, 2018)
The presented article substantiates the necessity of applying innovative technologies of the training process in the direction of training